A novel green process for tannic acid hydrolysis using an internally sulfonated hollow polystyrene sphere as catalyst. Issue 31 (10th May 2018) - Luo, Qionglin; Zeng, Shunqin; Shu, You; Fu, Zaihui; Zhao, Hongran; Su, Shengpei
Abstract : A polystyrene-hollow sphere catalyst was prepared by treating polystyrene-encapsulated calcium carbonate particles with concentrated hydrochloric acid. Abstract : A polystyrene-hollow sphere catalyst was prepared by treating polystyrene-encapsulated calcium carbonate particles with concentrated hydrochloric acid. This catalyst was characterized using TGA, FT-IR, optical microscope, SEM-EDX and XPS. Evidences from SEM-EDX and XPS analyses indicated that the sulfonate groups were on the inner surface of the polystyrene hollow sphere. The polystyrene hollow spheres were used as catalyst in the hydrolysis of tannic acid. Reaction conditions including the reaction temperature and time, loading of catalyst, ratio of tannic acid to H2 O and number of recycles were optimized. A high yield of gallic acid was obtained as the reaction performed under the following conditions: a temperature of 80 °C, a molar ratio of tannic acid to H2 O of 1 : 3, and a catalyst loading of 7% w/w (based on the mass of tannic acid). This catalyst showed excellent catalytic performance, easy separation, high stability and good reusability. This work provides a new strategy for the controllable synthesis of polystyrene hollow structures with sulfonic groups on the inner surface and an excellent and prospective catalyst for the production of gallic acid through hydrolysis of tannic acid.